Property Probes: Source Code Based Exploration of Program Analysis Results (Artifact) - Risberg Alaküla, Anton ; 0000-0003-0814-3367; Hedin, Görel ; 0000-0002-3003-2623; Fors, Niklas ; 0000-0003-2714-9457; Pop, Adrian (Zenodo, 2022)
This is the software artifact for the paper "Property Probes: Source Code Based Exploration of Program Analysis Results" published in ACM SIGPLAN International Conference on Software Language Engineering (SLE) 2022. The artifact was reviewed and awarded with the badges "Available" and "Reusable" (see https://www.acm.org/publications/policies/artifact-review-and-badging-current).